The effect of gender unemployment on economic growth: a panel data analysis - Taasim, Shairilizwan; Daud, Adrian (Global Academy of Training and Research, 2021)
Abstract Objective - Prior to the East ASEAN Growth Area (EAGA) in ASEAN, Brunei, Indonesia, Malaysia, and the Philippines (BIMP) took in an inflow of immigrants to support growth. The more they depended on foreign labour, the issue of gender inequality in the job sector became an issue that is hindering prosperity. Methodology/Technique - The research was aimed to identify the relation between unemployment rate from the gender perspective and economic growth of BIMP-EAGA by using two methods, namely Fully Modified Ordinary Least Square (FMOLS) and Dynamic Ordinary Least Square (DOLS). Annual time series data for the period of 1990 to 2018 was employed. Findings & Novelty - The result was contrary to Okun's law which says that there is a negative relation between the male unemployment rate and GDP. This study found that the female unemployment rate did not affect GDP and was insignificant. Policies that benefit and increase the participation of female workers in the job sector should be enhanced to prepare a conducive environment for the economy.